Biocontrol of Bacillus subtilis against Fusarium verticillioides in vitro and at maize root level - Cavaglieri, Lilia Reneé (2005)
Bacillus species as a group offer several advantages over other bacteria for protection against root pathogens because of their ability to form endospores, and because of the broad-spectrum activity of their antibiotics. The objectives of this work were to determine the ability of strains of Bacillus to inhibit Fusarium verticillioides growth and fumonisin B1 accumulation in vitro, and to evaluate the ability of the best bacterium for preventing rhizosphere and endorhizosphere colonization by F. verticillioides. Bacterial populations from the maize rhizoplane were obtained, and the capacity of ten Bacillus strains to inhibit fungal growth and fumonisin B1 accumulation in vitro was assayed. According to these results, B. subtilis CE1 was selected as the best antagonist for testing maize root colonization of F. verticillioides. Bacillus subtilis CE1 at 108 and 107 CFUml-1 inocula was able to reduce rhizoplane and endorhizosphere colonization of F. verticillioides in greenhouse trials. The strain B. subtilis CE1 could be a potential biological control agent against F. verticillioides at the root level.